テイチャク ヒョウイキ ノ パドル オヨビ カイホウ スイメン ナイブ ノ スイシツ ト ソレガ カイヨウ ニ アタエル エイキョウ ニ ツイテ - 大槻, 晃久; オオツキ, アキヒサ; Otsuki, Akihisa S. (2007)
P(論文) 夏季のリュツォ・ホルム湾の定着氷域内に形成されるパドル及び開放水面の環境について,観測を行ったので報告する.パドルのような小さな開口部は,定着氷とほぼ同じ厚さの淡水に近い低塩分水で満たされていた.この低塩分水は定着氷の融氷水が溜まったものと考えられる.定着氷が大きく消失せず天候も平穏であれば,パドルにたまった融氷水は下層へ拡散せず,定着氷下の海水を低塩分化させない.また開口部内の表層水の水温は下層の海水温より高く,特に2005年1月下旬にラングホブデ・袋浦で観測された水温は最高4°C であった.このように定着氷域における夏季の海洋表層の水温・塩分分布は変化に富んでいる. Summer environments in puddles and open waters formed in the fast ice area near Syowa Station, Antarctica were observed. Small open waters formed in the fast ice were filled with low saline water. Low saline water was supplied by melting sea ice and snow. If fast ice is not broken up by rough weather, melt water masses will stay stably in open water surrounded by fast ice. Consequently, this melt water will not dilute the surface sea water located under the fast ice. On the other hand, the water temperature of melt water was higher than underlying saline water. Especially, a maximum temperature of 4°C was observed in Hukuro Ura, Langhovde in late January 2005. Thus, structure of water temperature and salinity of summer open waters formed in the fast ice area have been rich in change. departmental bulletin paper